Sport and the international marketing environment - Kitchin, Paul (Henry Stewart Talks, 2008)
Sport and the international marketing environment, Competitive domestic markets and global trends, Market selection and market development, Rationalization and evaluation, Issues with globalization
Archived at 2022/04/04